2016
DOI: 10.1186/s12913-016-1489-0
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues on the use of administrative data in healthcare research: the case of heart failure hospitalizations in Lombardy region, 2000 to 2012

Abstract: BackgroundAdministrative data are increasingly used in healthcare research. However, in order to avoid biases, their use requires careful study planning. This paper describes the methodological principles and criteria used in a study on epidemiology, outcomes and process of care of patients hospitalized for heart failure (HF) in the largest Italian Region, from 2000 to 2012.MethodsData were extracted from the administrative data warehouse of the healthcare system of Lombardy, Italy. Hospital discharge forms wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 34 publications
0
43
0
3
Order By: Relevance
“…However, to ensure the accuracy of the information, a twofold strategy may be pursued: to link administrative data with suitable clinical registries or surveys (Gasperoni et al, 2017) and to check appropriateness of clinical questions that may be answered by these data, since 'the quality is not a property of the data set itself' but depends on the 'use to which it is put'. As an example, specific guidelines for dealing with administrative databases when acute and/or chronic cardiovascular diseases are considered are provided in Gasperoni et al (2017), Barbieri et al (2010), Mazzali et al (2016) and Ieva et al (2015).…”
Section: Francesca Ieva and Francescamentioning
confidence: 99%
“…However, to ensure the accuracy of the information, a twofold strategy may be pursued: to link administrative data with suitable clinical registries or surveys (Gasperoni et al, 2017) and to check appropriateness of clinical questions that may be answered by these data, since 'the quality is not a property of the data set itself' but depends on the 'use to which it is put'. As an example, specific guidelines for dealing with administrative databases when acute and/or chronic cardiovascular diseases are considered are provided in Gasperoni et al (2017), Barbieri et al (2010), Mazzali et al (2016) and Ieva et al (2015).…”
Section: Francesca Ieva and Francescamentioning
confidence: 99%
“…Furthermore, in ref. the authors showed that heart failure is a highly heterogeneous condition and thus various criteria were utilized to characterize different Heart Failure (HF) subgroups, leading to a sharper distinction of patients in four subgroups, which will be called HF groups, due to the classification of patient's disease. More precisely, the authors (see ref.…”
Section: Data Descriptionmentioning
confidence: 99%
“…More precisely, the authors (see ref. ) rely on the type and number of patient's diagnosis coded with ICD‐9‐CM (International Classification of Diseases, 9th revision, Clinical Modification) and on two slightly different criteria, which are the so called AHRQ and HCC , in order to finally cluster heart failure people.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The HF extract used in this study was part of a bigger dataset of all patients admitted in the region selecting patients with incident events between January 2006 and December 2012. For a detailed description of the extraction criteria to construct the data set of interest see Mazzali et al [17]. In brief, the Lombardy project's aims are to study the epidemiology, short-and medium-term outcomes and the variations in processes of care for patients hospitalized for HF.…”
Section: Data Source and Definition Of Cohortmentioning
confidence: 99%
“…First, some Lombardy HF admissions might actually have been for non-HF diagnoses and so should have been excluded from our cohort. The extraction criteria described in [17] are less restrictive than used in England, so this is possible to an extent. Second, some England non-HF admissions might actually have been for HF and so should have been included in our cohort.…”
Section: Lombardy Patients Had More Hf Admissions Each On Average Thamentioning
confidence: 99%